(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The truth is one but it is explained by great saints in differentlanguages and in different ways. We can practically experience this change inour life. How can we experience this one Truth? The point is, we are living inan ever-changing world. That potential is due to the spirit force. Tounderstand spirituality, first one must begin to understand the self. To be spiritualis not to change, to be spiritual is to enhance your being, so that in ourlives we can essentially be good human beings. When we receive the teachings ofspiritual meditation one realizes how to find the centre of his existence andthrough realizing his true self or his true nature, one realizes the essentialelement of the cosmic spirit which is a part of him. That is what we muststrive for, to elevate the spirit to such a level of existence. If we are stuckin traffic, no matter how beautiful the day was when we left home for work,that beautiful day will turn into a bad day if we are stuck for more than anhour or two. If all of us make it a goal in life to change and to be spiritualpeople, then changing the world is not a very difficult task.